Obstacles to the use of Educational Technology in Intermediate Schools from the viewpoint of Teachers in the State of Kuwait - Alkhaldi, Ahmed Kayyad; Aldhafeeri, Bandar Manshed; Alshammari, Mohammad Hazza (Journal of Educational and Psychological Sciences, 2021)
The research aims to identify the obstacles to the use of educational technology in preparatory schools from the point of view of male and female teachers in the State of Kuwait, and the research sample consisted of (350) male and female teachers, who were chosen in a simple random way from middle school teachers in public education schools in Mubarak Al-Kabeer Governorate (State of Kuwait) And their number (2512) teachers, according to the statistics of the Ministry of Education in the country. The State of Kuwait for the year 2021 AD, and the descriptive and analytical approach was adopted, and the questionnaire was used as a tool to collect data consisting of three areas (obstacles to the use of educational technology related to the teacher, and obstacles to its use). Related to educational technology, the research results showed: that the barriers to the use of educational technology related to the teacher came within the middle class, and the obstacles that stand in your way. And educational technology related to school management came within a large degree of appreciation, and obstacles to the use of educational technology related to school management. The use of educational technology related to the curriculum came within a large degree of appreciation. The research found that there are statistically significant differences between the responses of the research sample individuals due to the gender variable in favor of females. , And to the existence of statistically significant differences attributed to the variable of specialization in favor of the literary, and to the existence of statistically significant differences due to the variable of experience, and the differences came in favor of teachers with experience from 5 to less than 10 years. Based on the results obtained, the research recommended the following: Holding training courses for male and female teachers on how to use educational technology and apply it in the educational process. Because it provides real support for school curricula, in addition to providing an infrastructure for e-learning, by reorganizing classrooms and school halls, and equipping them to enable the teacher to use educational technology in the best way possible.